Importancia del plan de reducción de riesgos como medida de prevención ante emergencias y desastres naturales en la escuela Rafael Cajiao Enríquez de la parroquia Pastocalle, cantón Latacunga - Cayo Montes, María Elvira (2016)
The objective of this investigation in to prevent natural disasters through the development of a manual of basic instructions to follow in different types of emergencies or disasters in order to reduce human beings and material losses at Rafael Cajiao School, taking into account that in the province of Cotopaxi there are some threats and risks which, sine some years ago endanger human lives, in such way, it realized that the institution doesn´t receive continuous training to reduce risks….